Competition Law: Antitrust and Market Protection - Radea Respati Paramudhita (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
Competition law plays a strategic role in maintaining a healthy, fair, and competitive market. In Indonesia, competition regulations are stipulated in Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, which aims to prevent market domination, protect consumers, and create fairness for all business actors, including small and medium enterprises. This study aims to analyze the effectiveness of the implementation of competition law and the challenges faced in its enforcement, particularly amidst the development of the digital economy. The research method used is normative juridical with a qualitative approach through a study of relevant laws and regulations, legal literature, and academic studies. The results indicate that although the legal framework for competition in Indonesia is quite comprehensive, its implementation still faces institutional obstacles, limited executive authority of the Business Competition Supervisory Commission (KPPU), and new challenges resulting from the dominance of platform-based digital companies. Therefore, regulatory strengthening, institutional capacity building, and adaptation of competition law are needed to effectively and sustainably respond to modern market dynamics.